The Physical Health Condition and Income of the Pot Makers - Ramelito R. Paler; Mildred B. Miranda; Sharon A. Dolina; Evangeline Z. Hidalgo (Humanistic Network for Science and Technology (HNST), 2018)
This study determined the relationship between the physical health condition of the pot makers and their household gross monthly income. It used the correlational descriptive method and was conducted in 2018. There were 17 identified as respondents of the study. The tool used was a researcher made questionnaire and underwent validation process. The study was granted the notice to proceed by the university and were approved by the local executive heads. The researchers personally distributed the questionnaires to assist the respondents and further explained in vernacular the purpose of the study to their level of understanding. The questionnaire was translated into Filipino language. The percentage was used to determine the age, physical health condition and household gross monthly income. The spearman rank was used to determine the relationship between the physical health condition and the income. This paper arrived at the conclusions that there is a less participation in the pot making among the young generation. Likewise, most of the respondents were suffering mild illness and had a very low income. It is recommended that the state university in the locality needs to conduct trainings and provide technical assistance, establish programs to support the health condition of the people in the pot making, collaborate with government and non-government organizations addressing poverty alleviation. Further, household monthly gross income can be augmented by providing technology to provide fast production of better products and lessen the physical task. Keywords: Pot makers, Health, Household monthly gross income, Community development, Needs assessment, Poverty alleviation, Hypertension, Numbness, Basic needs